2023
DOI: 10.1007/s42000-023-00460-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential for NPY receptor–related therapies for polycystic ovary syndrome: an updated review

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine disease that can cause female infertility and bring economic burden to families and to society. The clinical and/or biochemical manifestations include hyperandrogenism, persistent anovulation, and polycystic ovarian changes, often accompanied by insulin resistance and obesity. Although its pathogenesis is unclear, PCOS involves the abnormal regulation of the hypothalamic-pituitary-ovarian axis and the abnormal activation of GnRH neurons. Neuropeptide Y (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…Hypothalamic NPY enhances GnRH-stimulated LH secretion and inhibits kisspeptin. It has been shown that NPY Y5 receptor antagonists significantly suppress weight gain and food intake ( 142 ). Further research and clinical trials are required before this neuropeptide can be used to treat the metabolic and reproductive dysfunctions observed in PCOS.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Hypothalamic NPY enhances GnRH-stimulated LH secretion and inhibits kisspeptin. It has been shown that NPY Y5 receptor antagonists significantly suppress weight gain and food intake ( 142 ). Further research and clinical trials are required before this neuropeptide can be used to treat the metabolic and reproductive dysfunctions observed in PCOS.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%